Pertimbangan Hakim Pada Putusan Nomor 458/PDT.SUS-PKPU/2021/PN.NIAGA.JKT.PST Terhadap Proses Terjadinya Penundaan Kewajiban Pembayaran Utang - Raden Ayu Widya Sari; Sari Oktalia; Evien Elmer; Kgs M Lukman Sigit; Josua Martua Siregar (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
An application for postponement of debt payment obligations (PKPU) can be filed before or after a bankruptcy petition with the aim of reaching an agreement between the debtor and creditors. If the agreement fails or is rejected by the court, the debtor is declared bankrupt. This study uses a normative legal method supported by empirical data. Judgment No. 458/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst indicates that the judge's considerations in the PKPU process are based on law, belief, and legal, sociological, and philosophical assessments of the trial facts. The appointment of PKPU administrators impacts various legal aspects, including debtor actions, reciprocal agreements, asset transfers, lease agreements, employment contracts, ongoing cases, debt settlements, and debt guarantors. It is recommended that judges master the legal foundations and understand supporting disciplines such as economics, business, and accounting, as well as the need for socialization or seminars related to bankruptcy and PKPU for the public and business actors.